PENGUJIAN PELARUT AIR, PELARUT H2O2 DAN LARUTAN Na2EDTA UNTUK KONSERVASI KERAMIK CAGAR BUDAYA BAWAH AIR - , RAISA DEBORAH, Prof. Dr. Endang Tri Wahyuni, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dissolution method for removal of sediment deposits covering the underwater heritage ceramic surface has been studied. This research was initiated by identification of chemical substances contained in sediment deposits covering the ceramic using Spectrophotometer IR and X-Ray Diffractometer (XRD). The concentration of metal in sediment deposits covering the underwater heritage ceramic surface was determined by Atomic Absorption Spectroscopy (AAS). The next step was dissolution of the sediment deposits by the sequential steps using water solvent with variation of pH, continued by dissolution using H2O2 solvent with variation of time, and the last step was dissolution using Na2EDTA solution with time variation. The results of sediment identification indicate that the chemical substances composing the ceramic sediment deposits are organic compounds, soluble salts in the forms of NaCl, Na2SO4, KCl and KNO3, and insoluble salts in the forms of CaCO3, Ca3(PO4)2, MgSO4, MgCO3, Fe2(CO3)3 and Fe2O3. The concentration of metal in sediment deposits covering the underwater heritage ceramic are Na= 32,82 mg/g